DIARY of a Wimpy Kid : WRECKING BALL - Kinney, Jeff (London : Puffin, 2019)
An unexpected inheritance gives the Heffley family a chance to make major improvements to their home. But they soon find that construction isn't all it's cracked up to be. When things get rough, will the Heffleys be able to stay ... or will they be forced to move?
Keywords: Heffley, Greg -- Juvenile fiction; Families -- Juvenile fiction; Dwellings -- Remodeling -- Juvenile fiction; Diary fiction; Children's stories; Humorous fiction